The consumer–producer dialogue - Khadduri, W (Oxford Institute for Energy Studies, 2015)
Among the early energy research subjects that Robert Mabro undertook was the producer–consumer dialogue – the topic that was at the top of the agenda during the late 1970s and early 1980s. The markets were in turmoil at the time, lacking direction and vision as to how the new balance of powers between oil producers and consumers would turn out. Conferences among leading producing and consuming countries were held to no avail; delegates pursued an elusive agreement, while there was much misunderstanding between the two parties, along with significant differences of interest on which neither side was ready to compromise. Mabro had little, if any, interest in these formal venues; he proposed instead the importance of launching an informal process, one which did not lead to any agreements, but which enhanced a better understanding among the actors. Mabro’s thought were reflected in a paper,1 quotations from which appear in this article.